Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cancers14092243
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Image Analysis-Based Prognosis Score Using Google’s Teachable Machine in Melanoma

Abstract: Background: The increasing number of melanoma patients makes it necessary to establish new strategies for prognosis assessment to ensure follow-up care. Deep-learning-based image analysis of primary melanoma could be a future component of risk stratification. Objectives: To develop a risk score for overall survival based on image analysis through artificial intelligence (AI) and validate it in a test cohort. Methods: Hematoxylin and eosin (H&E) stained sections of 831 melanomas, diagnosed from 2012–2015 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Recent studies have shown that TM, a code-free DL platform, can also be successfully used to analyze medical images. [22][23][24] Previous studies reported classification accuracy rates above 90% when transfer learning was used to train relatively large datasets. Despite the high accuracy levels of DL-based models in many ophthalmic diseases, there are still several clinical and technical challenges to their real-time application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that TM, a code-free DL platform, can also be successfully used to analyze medical images. [22][23][24] Previous studies reported classification accuracy rates above 90% when transfer learning was used to train relatively large datasets. Despite the high accuracy levels of DL-based models in many ophthalmic diseases, there are still several clinical and technical challenges to their real-time application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…TM was able to accurately predict prognosis for low-and high-risk groups. Researchers concluded that TM showed promise in considering melanoma risk using a slide image [36]. In one final example, TM was used to determine a tooth-marked tongue or not [37].…”
Section: Overview Of Tmmentioning
confidence: 99%
“…Scientific data are often classified into two categories. We provided three contextualized examples earlier-waterbirds or shorebirds [35], melanoma low risk or high risk [36] and tooth-marked tongue or non-tooth-marked tongue [37]. However, a binary classification system may not be the most effective for all scientific TM uses.…”
Section: Curricular Considerationsmentioning
confidence: 99%
“…Teachable machine is a platform used to develop technology from Machine Learning [37], [38]. Machine learning itself is a technology that can be used for learning media in the introduction of fish species in this study [39]. This technology allows the user to manage and provide the ability for computers to learn without the need for traditional programs in it.…”
Section: Teachable Machinementioning
confidence: 99%